To fee or not to fee: pricing policies in financial counseling - Mazzoli, Camilla; Nicolini, Gianni (Financial services review (Greenwich, Conn.), 2010)
Pricing represents a key variable in the financial advisory industry. For this reason we investigate the possibility of identifying the type of advisory provided by making use of the pricing policy that advisors adopt in the United States and Italy. The prevalence of 'opaque' forms of compensation leads us to identify which variables are able to predict the pricing policies (transparent vs. opaque) of a financial advisor. Results suggest that they are related to: the advisor's regulatory status (independent advisor or tied agent), the presence of certifications issued by independent authorities, the involvement in a financial products distribution process and the high or low frequency of the payments that are due for the advisory service. [PUBLICATION ABSTRACT]